Money and economic growth - Bhattarai, Keshab (The journal of economic asymmetries, 2014)
We study results of the cash in advance and money in utility models about the nature of fluctuations in economic activities and welfare in three interdependent economies. When the money is exogenously introduced in the form of cash in advance, it serves as a medium of exchange the rate of return in real and nominal assets become equal. Idiosyncratic technological shocks generate fluctuations in the growth rates of capital, output, prices, money, consumption, investment, labour supply and lifetime utilities of households. When households have money in their utility functions, the stock of money in excess of that required for transactions causes inflation and reduces the amount of capital stock and output in these economies. Both CIA and MIU models support for a steady growth rate of money according to the smooth growth rate of output. While the inflation targeting by manipulating the interest rates for macroeconomic stability are theoretically prudent policy moves it is impossible for central banks to eliminate business cycles that arise from shocks to production technology or structural features of the economy.
Keywords: Money; Growth